Accounting Consultation Units: An Organizational Memory Analysis* - SALTERIO, STEVEN; DENHAM, ROSS (Contemporary Accounting Research, 1997)
Abstract. Regulators have recently cited concerns about the extent and quality of accounting consultation within accounting firms on difficult client accounting policy issues. In this paper we report the results of research that examines the role of accounting consultation units in public accounting firms. We describe the five largest accounting consultation units in Canada. The accounting consultation units are then examined through the lens of organizational memory theory. We find differences among the accounting consultation units in their ability to act as a source of organizational memory for their firms. These differences include the following: the amount of resources devoted to the consultation function, the structure of the units, the mandate received by the unit from the firm, and the availability and amount of documentation about previous consultations. These differences suggest that firms' accounting consultation units differ in their ability to provide technical accounting advice. This variability may affect the actual or perceived quality of such advice to both clients and external regulators. In addition, this paper introduces organizational memory theory to the accounting literature. This theoretical approach may be useful in expanding the bounds of behavioral auditing research beyond the current emphasis on the individual auditor.